Review of Communications Received Related to General Assembly Matters (Ref. 298 -317), A/INF/73/Add.14, Eleventh session - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly Communications in support of the Special Committee recommendations, especially the withdrawal of Soviet troops; holding free elections; furthering international help; ending political terror and human rights violations. Also contains communications from Hungary protesting the UN resolution.